2012
DOI: 10.14238/pi52.5.2012.284-8
|View full text |Cite
|
Sign up to set email alerts
|

Congenital malformations in the neonatal unit of Arifin Achmad Hospital, Pekanbaru: occurrence and trends

Abstract: Background Congenital malformations are a global and continualissue, contributing to neonatal mortality. The incidence andprevalence, as well as distribution of congenital malformationsvary among countries.Objective To determine the 'prevalence, distribution, and trendsin congenital malformations which are important to develop plansto cope Mth the problem.Methods We reviewed all cases of congenital malformationsadmitted to the Neonatal Unit, Department of Child Health,Arifin Ahmad Hospital from 2008 to 2010. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
1
2
0
2
Order By: Relevance
“…The major reason for this difference is mainly methodological (retrospective review of registers and maternal medical records in two of the studies with possible under estimation due to incomplete or poor registration and the study population (the study was done in patients 0 to 17years old visiting the hospitals in the other). Even if variations are expected in the type of congenital anomalies depending on different factors( 1 , 2 , 15 ), similar to other studies( 4 , 5 , 7 , 10 14 ), our study demonstrated anomalies of the nervous system to be the commonest types of anomalies.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The major reason for this difference is mainly methodological (retrospective review of registers and maternal medical records in two of the studies with possible under estimation due to incomplete or poor registration and the study population (the study was done in patients 0 to 17years old visiting the hospitals in the other). Even if variations are expected in the type of congenital anomalies depending on different factors( 1 , 2 , 15 ), similar to other studies( 4 , 5 , 7 , 10 14 ), our study demonstrated anomalies of the nervous system to be the commonest types of anomalies.…”
Section: Discussionsupporting
confidence: 90%
“…Hence, mothers with no or inadequate ANC follow up might be at risk of having newborns with congenital anomalies. Different studies( 4 , 7 ) including a study done in Ethiopia before( 14 ), have also demonstrated this, mothers with no or inadequate ANC visits having increased risk of congenital anomalies in their newborns( 4 , 7 ). Our study has also demonstrated same, indicating the need of improving antenatal care attendance by pregnant mothers as early in their pregnancy course as possible and improving the quality of ANC provided by healthcare workers particularly targeting the preventive measures towards congenital anomalies.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Hubungan antara prinsipal dengan agen apabila tidak dijalani dan dikelola dengan baik, akan memicu adanya asimetri informasi. Asimetri informasi merupakan ketidakselarasan informasi dari yang menyediakan kepada pihak yang menerima informasi (Wisnumurti, 2012). Berdasarkan teori agensi, asimetri informasi juga dipahami sebagai kondisi dimana agen lebih banyak memiliki informasi tentang perusahaan ketimbang prinsipal (Wisnumurti, 2012).…”
Section: Landasan Teoritis Dan Pengembangan Hipotesisunclassified
“…Asimetri informasi (X2) didefinisikan sebagai ketidakselarasan informasi karena pihak agen cenderung memiliki informasi yang lebih banyak daripada prinsipal (Wisnumurti, 2012). Pengukuran asimetri informasi menggunakan kuesioner dengan indikator berupa sistem informasi akuntansi, hubungan input dan output, potensi kinerja, dan teknis pekerjaan (Ariani et al, 2014).…”
Section: Metode Penelitianunclassified